2019
DOI: 10.1093/jxb/erz004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the proteolytically inactive FtsH members has impacts on the Darwinian fitness of Arabidopsis thaliana

Abstract: The evolution of multiple genes encoding presumably proteolytically inactive filamentation-temperature-sensitive protein H (FtsHi) proteases accompanied the evolution of FTSH12 , and Arabidopsis mutants with reduced FTSHi expression show decreases in Darwinian fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 50 publications
2
65
0
Order By: Relevance
“…The relevance of this question is reinforced due to the evolutionary history of FTSH proteins, during which a number of proteolytically inactive FTSHs (designated FTSHi) have been evolved. In the case of Arabidopsis, there are five such proteins, all of them are essential for development and growth (Sokolenko et al, 2002; Wagner et al, 2012; Mishra et al, 2019). Four of these have been recently identified in a large chloroplast complex, together with FTSH12, serving as a motor for protein import into chloroplasts (Kikuchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this question is reinforced due to the evolutionary history of FTSH proteins, during which a number of proteolytically inactive FTSHs (designated FTSHi) have been evolved. In the case of Arabidopsis, there are five such proteins, all of them are essential for development and growth (Sokolenko et al, 2002; Wagner et al, 2012; Mishra et al, 2019). Four of these have been recently identified in a large chloroplast complex, together with FTSH12, serving as a motor for protein import into chloroplasts (Kikuchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Relative transcript levels were determined by quantitative reverse transcription PCR (qRT–PCR) as described previously (Mishra et al , 2019), using the primers listed in Supplementary Table S2. RNA was extracted from the seedlings that were used to determine the impact of DEG10 and temperature on root growth.…”
Section: Methodsmentioning
confidence: 99%
“…While the location of FtsH11 ( Wagner et al , 2016 ) and FtsH12 ( Li et al , 2017 ) in the inner envelope could be confirmed, an unexpected localization of FtsHi4 in the thylakoid membrane has been reported ( Lu et al , 2014 ). With the exception of FTSHi 3, FTSHi knock-out mutants are embryo lethal ( Meinke et al , 2008 ), with reduced expression showing diminished Darwinian fitness ( Mishra et al , 2019 ). A point mutation in FTSHi1 that impaired its ATPase domain function ( ftsh1-1/arc1; Kadirjan-Kalbach et al , 2012 ) as well as knock-down mutants of FTSHi4 ( Lu et al , 2014 ) and FTSHi5 ( Wang et al , 2018 ) showed cotyledon and growth phenotypes, including alterations in chloroplast ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…FtsH12 was thus suggested to be an essential component of an ATP-driven motor complex, while its proteolytic activity was reported to be dispensable ( Kikuchi et al , 2013 ). However, neither FtsH12 orthologues nor FtsHi are found in Poaceae ( Nakai, 2018 ; Mishra et al , 2019 ; Li et al , 2020 ), suggesting that it is not ubiquitous in all higher plants. Therefore, the importance of both the FtsH12-FtsHi complex and the interacting 1 MDa TIC complex for plastid protein import are subjects of a controversial debate ( Nakai, 2015 ; Agne et al , 2017 ; Bölter and Soll, 2017 ; Li et al , 2020 ; Nakai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%